2021
DOI: 10.1038/s41598-021-03915-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between magnesium concentrations and prediabetes: a systematic review and meta-analysis

Abstract: Studies on the association between serum magnesium level and prediabetes yielded inconsistent results. Therefore, the present meta-analysis was designed to examine the association between serum magnesium levels and prediabetes. Online databases including PubMed, Embase, Scopus and Google Scholar were searched up to October, 2020. A total of 10 studies that reported mean and standard deviation (SD) of magnesium levels in prediabetes and healthy control group were identified. Random effects models were used to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Magnesium (Mg) is an essential mineral for the human body, which plays a significant role in glucose and insulin metabolism [ 4 ]. A recent meta-analysis [ 5 ] showed that circulating Mg levels in prediabetes were significantly lower than in healthy controls, confirming that Mg deficiency may play a role in the development and progression of prediabetes [ 6 , 7 , 8 ]. Dietary Mg is the main source of human Mg, which directly affects the Mg nutritional status of the body [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Magnesium (Mg) is an essential mineral for the human body, which plays a significant role in glucose and insulin metabolism [ 4 ]. A recent meta-analysis [ 5 ] showed that circulating Mg levels in prediabetes were significantly lower than in healthy controls, confirming that Mg deficiency may play a role in the development and progression of prediabetes [ 6 , 7 , 8 ]. Dietary Mg is the main source of human Mg, which directly affects the Mg nutritional status of the body [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from multiple SRMAs has supported the association of specific vitamins and minerals, analogous to those found in nuts, with markers of glycemic control and prevention of T2D [ 80 , 81 , 82 , 83 , 84 , 85 ]. When oral supplementation of antioxidant vitamins and minerals (such as those found in nuts: vitamin E, selenium, and zinc) were assessed in a SRMA of RCTs considering people with T2D, supplementation of zinc (30 to 660 mg/day) and vitamin E (200 to 800 IU/day) reduced HbA1c, and zinc reduced fasting blood sugar.…”
Section: Possible Mechanisms Of Action Of Nuts In Diabetes Prevention...mentioning
confidence: 99%
“…Imbalances in magnesium status, specifically hypomagnesemia, have been shown to inhibit glucose transporter type 4 translocation, increase insulin resistance, and affect lipid metabolism, oxidative stress, and the antioxidant system of endothelial cells [ 82 ]. A SRMA of 12 observational studies showed significantly lower circulating magnesium levels in people with prediabetes compared to individuals with good health [ 83 ]. Further, a 100 mg/day increase in oral magnesium intake has been associated with a 15% reduction in T2D risk (SRMA prospective cohort studies, n = 286,668).…”
Section: Possible Mechanisms Of Action Of Nuts In Diabetes Prevention...mentioning
confidence: 99%
“…Insufficient intake A diet low in Magnesium [102,105] Slimming cures [102,106] Intensification of losses At the gastrointestinal level: vomiting; purgatives/laxatives; trailing diarrhea [103,107,108] By the renal route: nephropathies; diuretics; chronic alcoholism; diabetes [104,[109][110][111][112][113][114][115] Table 2. Cont.…”
Section: Causes Of Magnesium Deficiencymentioning
confidence: 99%
“…Decreased intestinal absorption Conditions after intestinal resection [103,116] Diarrhea [103,107,108] Malabsorption [103,107,108,117] Chron's disease [103,108,117] Ulcerative colitis [103,117] Coeliac disease [103,107] Stressing Factors Pregnancy [32,34,102,118,119] Lactation [32,34,102,118,119] The growing period [102,120] Sport performance [102,[121][122][123] Old age [103,107,109,119,124,125] Convalescence [86,87,102] Endocrine disorders Hyperthyroidism [104,126,127] Aldosteronism [104,126,127] Hyperparathyroidism…”
Section: Causes Of Magnesium Deficiencymentioning
confidence: 99%